Robust interference cancellation for differential quadrature phase-shift keying modulation with band limiting and adaptive filter - Rahmad Hidayat; Ahmad Sujana; Andrew Ghea Mahardika; Herawati Herawati; Givy Devira Ramady; Ninik Sri Lestari (Universitas Ahmad Dahlan, 2021)
Differential quadrature phase-shift keying (DQPSK) modulation techniques and their variants are widely applied in digital communication, such as for high-speed optical fiber, bluetooth, or satellite communication. In its implementation, DQPSK cannot be separated from the potential harmful interference. In this research, a system model has been made for observation and analysis of the interference cancellation process. Discrete finite-duration impulse response (FIR) filters for band limiting and adaptive filter are the key components of the supporting block for this system model. Robust Simulink results have shown a significant increase in system performance in the existence of these key components. The indication has been shown by the best bit error rate (BER) of 3.3e-05. Constellation and eye pattern diagrams have supported the BER.